2017
DOI: 10.4097/kjae.2017.70.6.633
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized controlled double-blind trial to assess the effects of dexmedetomidine during cleft palate surgery

Abstract: BackgroundWe investigated whether the intraoperative administration of dexmedetomidine would attenuate the profound sympathoadrenal response associated with cleft palate (CP) surgery.MethodsSixty children aged 6 months to 12 years undergoing CP surgery under general anesthesia were randomly assigned to the control (C) or dexmedetomidine (D) groups. Group C received benzodiazepine (0.05 mg/kg midazolam followed by infusion of normal saline) fentanyl isoflurane anesthesia, and Group D received dexmedetomidine (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…Moreover, we could not extract data from two studies. Finally, 33 ( 8 40 ) independent studies were included in the meta-analysis. Figure 1 presents the detailed selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we could not extract data from two studies. Finally, 33 ( 8 40 ) independent studies were included in the meta-analysis. Figure 1 presents the detailed selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al (2012) found that a loading dose of 1 mgÁkg À1 followed by a maintenance dose of 0.75 mgÁkg À1 had decreased pain scores and discharge time in patients undergoing cleft lip and palate surgery. Surana et al (2017) demonstrated that a loading dose of 1 mgÁkg À1 and an infusion of 0.5 mgÁkg À1 Áh À1 reduced intraoperative opioid and volatile anesthesia requirements, and prolonged the time to first postoperative rescue analgesic with similar PACU discharge times. Obayah et al (2010) showed that dexmedetomidine added to bupivacaine for a palatine nerve block, significantly reduced pain scores and prolonged the time to first analgesic request when compared with bupivacaine injection alone.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, the number of patients ≤1 is small and this sample is not sufficiently powered to detect a difference between groups. However, α-2 adrenergic receptor agonists have been used for cleft surgery without increasing complications (Jindal et al, 2011; Kayyal et al, 2014; Peng and Zhang, 2015; Surana et al, 2017). A final limitation is that we did not include an intravenous CLG in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding 50 studies, 13 studies including 1040 children aged 3 months to 12 years were finally included in this analysis. [12][13][14][15][16][17][18][19][20][21][22][23][24] The flow diagram of the literature search strategy is shown in figure 1.…”
Section: Study Selectionmentioning
confidence: 99%